Pocket calculator: a humdrum 'obviator' in Papua New Guinea?. (7th August 2013) - Pickles, Anthony J.
Abstract : This article examines the significance of pockets for controlling money in Highland Papua New Guinea. Contextualizing elaborate 'systems' for compartmentalizing monies in separate pockets, I draw upon the connection Highlanders make between transaction and skin. Pockets, I argue, offer opportunities to hide one's wealth reserves while gifting, keeping intentions opaque and leaving interlocutors guessing at the meaning of donors' speech, and forcing recipients to perceive their gift as ample. The article suggests that expectations are deliberately conventionalized in order to be exceeded, drawing parallels with Roy Wagner's notion of obviation. After characterizing Gorokan pockets and their gifting 'logic', I analyse how pocket‐users are themselves conventionalized as forthright or selfish in local discourse, based upon the pockets they display and where their clothes come from. Giving people clothing that includes pockets is therefore a way to regain control over their capacity to reveal wealth from their pockets.